Studying the effects of natural mucilage preparation procedures on its physical properties and drag reducing efficiency - Siti Nuraffini, Kamarulizam (2009)
In this present experiment, the objective is to investigate the effectiveness of new formulated natural polymer as drag reducing agent (DRA). Two different methods with additives concentrations at 80ppm, 150ppm and 300ppm weight percent were tested in set up rig with three different pipe diameters which are 0.0127 meter D.I, 0.0254 meter D.I and 0.0381 meter D.I and testing section length of 1.5 meter. The result shown highest %DR was 67.2619% with 300ppm concentration in Thermal Method. In the other hand, average %DR was higher for Cold Method in 300ppm. %DR was found to be increase when additive concentrations and flow rate that related to Reynold’s Number increase. Adding few ppm concentration additives in water shown there are slightly effects in its physical properties. %DR were increased until maximum %DR before mechanical degradation occur due to mechanical degradation in pump rotation during pressure drop experimentation. The method to synthesis natural polymeric DRA also give slighty different in %DR. The result is adding DRA will give higher %DR on pipeline flows without adding pumps.